Disnep: winnie the pooh: the honey tree - Totten, Bob (Scholastic Australia Gosford, NSW, 2021)
"When Winnie the Pooh hears a strange buzzing noise, he realises that it must be bees. So he attempts to climb a rather tall tree in his search for the bees, as this will no doubt lead him to honey! Does Pooh manage to reach the top of the tree? Does he get his honey?" -- Back cover